The sacred cause civil military conflict over Soviet national security, 1917 - 1992 - Nichols, Thomas M. 1960- (Cornell Univ. Press, 1993)
To the officers of the USSR Armed Forces, the defense of the Soviet Union was, in the words of a Soviet general, a "sacred cause." What was the nature of Soviet civil-military relations, and what have the new militaries inherited from the Soviet experience? In this book Thomas M. Nichols examines the struggles over national security policy between military officers and political leaders in the USSR, and shows that the Soviet civil-military relationship has a long history of conflict rather than cooperation. Nichols disputes the longstanding Western belief in Party-Army amity. He argues that Party control over the Soviet armed forces has been tenuous since Stalin's death; the relationship was inherently unstable and conflictual, growing in intensity because of Gorbachev and his approach to domestic and foreign policy reforms. The source of this instability lay in the creation of the Soviet Armed Forces as a Marxist military, and Nichols maintains that this privileged and highly ideological institution found itself in frequent conflict with a Party that had of necessity to take an increasingly pragmatic approach to international politics. Movement toward a politically isolated and professionalized military, he shows, was continuously subverted by civilian leaders who sought to control military issues through political intrusions into doctrine and strategy. He concludes that the new leaders of the post-Soviet republics have inherited a group of military organizations that continue to resist the abandonment both of their ideological foundations and of their cohesion as a multinational military - a situation he believes may prove to be one of the greatest threats to the emerging post-Soviet democracies.
Keywords: Defensie; Krijgsmacht; Relaciones civiles militares - Rusia; Civil-military relations -- Soviet Union; Geschichte; Staat; Militär; Sowjetunion; Soviet Union -- Armed Forces